Effect of of pre- and post- emergence herbicides on weed infestation, crop growth and economics of maize - Pardeep Kumar; Meenakshi Sangwan; Todar Mal; Sushil Kumar (Annals of Agricultural Research, 2024)
A field experiment was conducted during the kharif season of 2020-21 to evaluate the efficacy of pre and post emergence herbicides under sole, mixture and their sequential application against control of mixed weed flora in maize. Weed flora in experimental field was diverse among grassy weeds, Echinocloa colona was a major weed constituting about 47.5% of the total weed population at 20 days after sowing (DAS) and 38.8% and 40% at 50 and 80 DAS, respectively and followed by Dactyloctenium aegyptium Pre- emergence (PRE) application of atrazine 1000 g followed by tembotrione + surfactant (S) 120 + 1000 g ha-1 at 35 DAS signifi cantly reduced sedges, grassy and broad leaf weeds density at 20, 50 and 80 DAS which was at par with atrazine 750 g ha-1 PRE fb tembotrione + S 120 + 1000 g ha-1 at 35 DAS. Among herbicidal treatments, signifi cantly higher visual weed control, plant height, grain yield and B: C ratio was observed under sequential application of atrazine 1000 PRE fb tembotrione + S 120 + 1000 g ha-1 at 35 DAS which was at par with atrazine 750 PRE fb tembotrione + S 120 + 1000 g ha-1 at 35 DAS, but higher than all the other treatments.